PENYELENGGARAAN PELAYANAN PRIMA PADA BIDANG INFORMASI MELALUI MEKANISME PELAYANAN PENGADUAN OLEH BPMP DI KOTA BANDAR LAMPUNG - Nurmayani, Nurmayani (Fakultas Hukum Universitas Lampung, 2012)
The reseach is to studied about the arrangement of excellent serfice at information field trough claimed service mechanism. The research used normative-empirical jurisdication. The result of research indicated that of excellent service at infomation filed through claimed service mechanism, had the solution of claimed process during ten workdays and it can be solved in oral claim directly by a license applicant.